A COMPARATIVE STUDY BETWEEN ARMS AND LEGS IN SOME FUNCTIONAL VARIABLES AFTER PERFORMING AEROBIC EFFORT - Hakam Salem Elias (Proximus Journal Publishing, 2025)
The research aims to identify the response of some respiratory functional variables (pulmonary ventilation, breathing volume, and respiratory rate) and heart rate after performing an aerobic effort for the arms. Identify the response of some respiratory functional variables (pulmonary ventilation, breathing volume, and respiratory rate) and heart rate after performing aerobic effort for the legs. Identify the differences between the aerobic potential tests of the arms and legs in terms of some functional variables and the extension of the circulatory and respiratory systems
Keywords: respiratory; performing; arms; legs; pulmonary ventilation